Communication Management and Planned of Behavior Inmates Self-Reliance through the Food Security Program at Nusakambangan Correctional Institution - Yeni Nuraeni; Tunggadewi Ratu Wardhani (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
Nusakambangan correctional institution is one of the implementers of the food security program. This program not only achieves food self-sufficiency but also has succeeded in providing better and positive phenomenon. Research purpose to examine the role of communication management and implementation of planned behavioral theory achieving inmates self reliance and successful social reintegration through the food security program. Using a descriptive qualitative approach through observation, interviews, and documentation. Eight inmates actively participated supported by correctional institution officers in three sectors: agriculture, livestock farming and fisheries. The findings of this study indicate that interactional communication and the integration of communication management with planned of behavior can explain important aspects for the success of the program. Communication management through: planning, organizing, implementing, and controlling functions, as well as the implementation of planned behavioral through: attitudes towards behavior, subjective norms, perceived behavioral control, intentions and actual behavior, can create synergy between correctional institution officers and inmates. The conclusion explains that the success program is not only seen from a technical perspective but also integration communication management and implementation planned of behavior, which can realize inmates self reliance and successful social reintegration when returning to society. The implications of this research are Organizational Factors: effective communication, coordination, and positive institutional image. Behavioral Factors: development of positive inmate attitudes, strengthening productive work norms and improving self-control. Self Reliance Factors: skills development, open economic opportunities and greater confidence in achieving social reintegration upon returning to society.